The T-Cell Immune Response against Kaposi's Sarcoma-Associated Herpesvirus. (23rd December 2010) - Robey, Rebecca C.; Mletzko, Salvinia; Gotch, Frances M.
Abstract : Kaposi's sarcoma-associated herpesvirus (KSHV) is the aetiological agent of Kaposi's sarcoma (KS), the most frequently arising malignancy in individuals with untreated HIV/AIDS. There are several lines of evidence to indicate that Kaposi's sarcoma oncogenesis is associated with loss of T-cell-mediated control of KSHV-infected cells. KSHV can establish life-long asymptomatic infection in immune-competent individuals. However, when T-cell immune control declines, for example, through AIDS or treatment with immunosuppressive drugs, both the prevalence of KSHV infection and the incidence of KS in KSHV carriers dramatically increase. Moreover, a dramatic and spontaneous improvement in KS is frequently seen when immunity is restored, for example, through antiretroviral therapy or the cessation of iatrogenic drugs. In this paper we describe the current state of knowledge on the T-cell immune responses against KSHV.